Analisis Nilai Karakter Gotong Royong pada Film Animasi A Bug’s Life - Sagita Rima Pramesti; Muhamad Taufik Hidayat (University of Muhammadiyah Malang, 2023)
Education is a service that must be taken and accepted by every human being. The main objective of instilling primary education in children is to develop children's intelligence, personality, character and personality to produce children with noble characters. This study aimed to analyze the value of the cooperation character depicted in the animated film A Bug's Life. The method used in this study was descriptive qualitative with analysis content. The data was obtained from the animated film A Bug's Life. This study employed a documentation technique. Data analysis was done by reducing data, presenting data, and drawing conclusions. The assessment technique to check the validity of the data was a credibility test with techniques of extending observations and increasing perseverance. The findings showed that the animated film A Bug's Life has seven sub-values of cooperation characters. They are (1) Cooperation with the type of activities of collecting food together, creating and flying artificial birds; (2) Helping with the type of activities of helping friends who experience a disaster, such as getting lost, falling, and saving baby ants from the blaze; (3) Empathy with activities of empathizing with friends who are crushed by leaf stems, falling, and tumbling over; (4) Positive dependence on activities of assisting friends who need help; (5) Concern with social care activities with the attitude of caring about the life of the lives of creatures around them and caring for the damaged environment; (6) Solidarity with the activity of assisting friends who are facing problems; (7) Deliberation with an activity of finding a way out to fight the evil grasshopper mob